Two mouse genes encoding potential transcription factors with identical DNA-binding domains are activated by growth factors in cultured cells. - Lemaire, P (1988)
We previously reported the identification of a mouse gene, Krox-20, encoding a protein with three "zinc fingers" (DNA-binding domains with coordinated zinc ions) whose expression is regulated during G0/G1 transition (cell-cycle reentry). We now have isolated cDNAs corresponding to a related gene, Krox-24. Krox-24 encodes a protein with zinc fingers nearly identical to those encoded by Krox-20 and similar to those of transcription factor Sp1. Similarity between Krox-20 and Krox-24 proteins also extends to several blocks of amino acid sequence located upstream of the finger region. Like Krox-20, Krox-24 is transiently activated in quiescent cells after treatment with fetal bovine serum or purified growth factors. The kinetics of activation are similar to those of the protooncogene c-fos. The induction does not require de novo protein synthesis, and cycloheximide treatment of the cells leads to superinduction due, at least in part, to mRNA stabilization. In the mouse, the two genes are expressed in a tissue-specific manner, with slightly different patterns. These properties suggest that Krox-20 and Krox-24 may encode transcription factors with identical DNA target sequences and that these factors may be involved in the modulation of cell proliferation and differentiation.